ANALISIS SWOT TERHADAP PELAYANAN PENDAFTARAN JEMAAH HAJI - Lilis Renfiana (Multazam : Jurnal Manajemen Haji dan Umrah, 2022)
Abstract: The first service provided by the Ministry of Religion of Mesuji Pematang Panggang to prospective pilgrims is registration service before other services such as ritual guidance services, services during the implementation of the pilgrimage and others. Considering that the majority of prospective Indonesian pilgrims are parents, the best and maximum service needs to be done in order to provide comfort and satisfaction for prospective pilgrims. This study aims to determine and examine how the analysis of Hajj registration services at the Ministry of Religion Mesuji. The method used in this study is a qualitative method that produces descriptive data using data collection techniques in the form of observation, in-depth interviews with the parties concerned and books that support the completeness of the data. The results of this study indicate that the analysis of registration services carried out by the Ministry of Religion Mesuji Pematang Panggang as a government agency that is more highlighted by the community and closest to the community needs to provide facilities in the form of good and primary services, because good service will always be a consideration for the community. to be able to respond to all the kindness given